Analysis of The Use of Partograph in Normal Delivery Care by Midwives As a Detection of Labor Complications - Herliana Herliana (Jurnal MIDPRO, 2021)
Globally, the Maternal Mortality Ratio (MMR) is unacceptably high. The high number of maternal deaths during pregnancy and childbirth is caused by preventable complications during these periods such as hemorrhage, infections, eclampsia, hypertensive disorder during pregnancy, and obstructed labor. To prevent these obstetric problems, the World Health Organization (WHO) suggests using partograph for birth attendants, especially in low-resource settings. The aim of this study is to analyze the use of partographs in labor care by midwives as detections of difficulties in the labor process. This study used a qualitative approach with in-depth interview techniques, focus group discussions and observations with midwives, head of PHC, and DHO officer as respondents. The results showed that the behavior of midwives in the use of partographs was still low. Lack of documentation regarding referral records. Motivation in using partographs is also low. Furthermore, there is a lack of supervision carried out by DHO Officers, professional organizations and leaders from each institution in health services. There is no direct monitoring of the evaluation of filling out the partograph sheet from the leaders. For reporting documentation, partograph sheets are made for archiving and claims for service payments. It is important that the DHO Officer improves monitoring and evaluation gradually and continuously to health care services. The Indonesian Midwives Association should supervise and provide guidance to each of its members.